Metafísica, política e moral na filosofia de Bergson - Julião, Luanda Gomes dos Santos (2021)
The objective of this research is to go through the thought of the french philosopher H. Bergson, unraveling some points exposed since his great inaugural work, Essay on the immediate data of conscience, until his last book, The two sources of morals and religion, observing mainly how this philosophy, which largely focused on metaphysics and the delineation of duration, began to take an interest in society, morals, and politics.